Magmatic Mn-rich garnets in volcanic settings: Age and longevity of the magmatic plumbing system of the Miocene Ramadas volcanism (NW Argentina) - Lucci, Federico (2018)
The Miocene “Corte Blanco Tuff” rhyolite deposit is the product of a large volume and high intensity Plinian eruption from the solitary and monogenetic Ramadas Volcanic Centre (Central Andes, Province of Salta, NW Argentina). The “Corte Blanco Tuff” consists of vitreous tube pumices with rare euhedral sub-millimetric Mn-garnet phenocrysts, typically hosting inclusions of U-phases as zircon and monazite. Here, we present new textural, major and trace elemental analyses of garnet, zircon and glass that, combined with in situ U-(Th)-Pb zircon and monazite dating, are used to reconstruct the thermobaric environment of formation, age and longevity of the magmatic plumbing system of the Ramadas magma. The results indicate to a crystallization path of a peraluminous rhyolitic melt at shallow crustal levels (≤6 km), as sequentially tracked by the initial nucleation of zircon (780 °C at 9.16 Ma) and garnet (above or at ca. 700 °C), to the final monazite growth (660–670 °C, at 8.70 Ma) in a water-saturated (H2O = 3–5 wt%) environment, shortly before the eruption started. These data (1) define for the first time the primary magmatic origin of Mn-garnet in a rhyolitic volcanic setting; (2) provide new partition coefficients of rare earth elements (REE) between natural garnet, zircon and rhyolitic melts; and (3) permit reconstruction of the magmatic processes that resulted in the Ramadas eruption. On a wider scale, our results document the spatio-temporal (P-T conditions, timing and longevity) time scales involved in the petrogenesis of a shallow peraluminous water-saturated rhyolitic magmatic plumbing system that is able to generate the conditions for extremely explosive Plinian eruptions.